مساهمة الآباء في الأنشطة اللاصفية من وجهة نظر أبنائهم الموهوبين - تامتلث,ابراهيم; كراوه,عمر; بن يحي,أسماء (University of Eloued جامعة الوادي, 2024)
هدفت الدراسة إلى الكشف عن مساهمة الآباء في الأنشطة اللاصفية من وجهة نظر أبنائهم الموهوبين في مرحلتي المتوسط والثانوي بكل من مؤسستي الشيخ عمي سعيد والرضوان بولاية غرداية، تمّ استخدام المنهج الوصفي على عيّنة مكونة من 90 تلميذا (ة) منتظما في الأنشطة اللاصفية، كما اختيرت العيّنة الأساسية بطريقة قصدية عن طريق ترشيح المشرفين عليهم في الأنشطة اللاصفية وشملت في الأول 136، وبعد ذلك تمّ تطبيق مقياس رنزولي عليهم للتأكد من ترشيح المشرفين للفئة المقصودة فأصبحت العيّنة 90 تلميذا (ة)، وعليها تم تطبيق استبانة مساهمة الآباء في الأنشطة اللاصفية من وجهة نظر الموهوبين المعدة من طرف الباحث والتي تتكون من 20 بندا موزعة على أربعة أبعاد "المرافقة، التحفيز المادي، التحفيز المعنوي، التشارك"، وبعد المعالجة الإحصائية باستخدام البرنامج الإحصائي spss النسخة 24، تم الوصول إلى أن مساهمة الآباء للأبناء الموهوبين تتوزع بين –المرافقة، التحفيز المادي، التحفيز المعنوي، التشارك في الأنشطة- وإلى عدم وجود فروق بين الجنسين والمرحلة الدراسية في المساهمة. Abstract: The study aimed to reveal the contribution of parents to extracurricular activities from the point of view of gifted students in the middle and secondary stages in both Sheikh Ammi Said and Al-Radwan institutions in Ghardaia province. The descriptive method was used on a sample of 90 regular students participating in extracurricular activities. The basic sample was chosen intentionally by nominating their supervisors in extracurricular activities and included 136 at first. After that, a Renzulli scale was applied to them to ensure that the supervisors were nominated for the intended category, so the sample became 90 students. Accordingly, a questionnaire was applied on the contribution of parents to extracurricular activities from the point of view of gifted students, prepared by the researcher, which consists of 20 items distributed over four dimensions: "accompaniment, material incentive, moral incentive, participation". After statistical processing using the statistical program SPSS version 24, it was concluded that the contribution of parents to gifted children is distributed between - accompaniment, material incentive, moral incentive, participation in activities- and that there are no differences between genders and stage Academic contribution
Keywords: أنشطة لاصفية; مساهمة الآباء; موهوبين; extracurricular activities; parental contribution; gifted